Blended Learning During the Pandemic: A Bibliometric Analysis of Students’ Perceptions - Pakaya, Mohamad Hendri Y.; Nurhamdin, Taravisca Oktavia; Kaaba, Titin (English Education Department, 2023)
This study aims to analyze trends and developments in research on students' perceptions of blended learning during the COVID-19 pandemic using a bibliometric approach. The bibliometric method is used to quantitatively evaluate and interpret academic publications, providing insights into the growth, impact, and thematic evolution within this research domain. Data was collected from major academic databases such as Sinta and Google Scholar, focusing on publications from the last decade to capture recent developments in blended learning research during the pandemic. The results show a significant increase in the number of publications on blended learning starting in 2019, peaking in 2021, before slightly declining in 2022. The analysis also reveals that student perception is the most frequently researched topic, with data collection methods dominated by tests and questionnaires. However, there is a lack of R&D studies and qualitative research that could provide further insights into the development and refinement of blended learning approaches. This study concludes that while academic interest in blended learning has increased, particularly during the pandemic, more R&D studies and qualitative research are needed to develop and refine these learning methods and to enhance understanding of their effectiveness in various educational contexts.